Development of the method for decomposition of superpositions of unknown pulsed signals using the secondorder adaptive spectral analysis - Stepanenko, Alexander; Oliinyk, Andrii; Deineha, Larysa; Zaiko, Tetiana (Eastern-European Journal of Enterprise Technologies, 2018)
We considered the issue of "intuitive" analysis, processing, and synthesis of unknown pulse sequences in a detailed form. We studied both classical methods of analysis with all pluses and minuses and the developed prospective method created on their basis. The developed method is adaptive, it is based on the consistent use of various methods of spectral analysis, which increases reliability, sensitivity, and resolution capability of visual analysis of echo-pulse images. Thus, we solved the problem on processing pulse signals. The proposed method makes it possible to increase resolution capability in the processing of signals and images without using a priori information on the form of elementary pulses. It is resistant to the influence of measuring noise. We presented the results of numerical simulation and actual verification on the example of a seismic image. The considered method has a significant development potential, both in theoretical and application aspects (first of all, in areas of ultrasonic medical diagnosis, seismic imaging, and non-destructive testing).